Unveiling the role of long non-coding RNAs in chicken immune response to highly pathogenic avian influenza H5N1 infection - Thi Hao Vu; Chaeeun Kim; Anh Duc Truong; Jun-Mo Kim; Hyun S. Lillehoj; Yeong Ho Hong (Poultry Science)
Avian influenza viruses (AIVs) pose a significant threat to global poultry production, necessitating effective control strategies to mitigate economic losses and ensure animal welfare. Long non-coding RNAs (lncRNAs) have emerged as crucial regulators of immune responses, yet their roles in AIV-infected chickens remain poorly understood. This study aimed to investigate the expression profiles of lncRNAs and their targets in Vietnamese Ri chickens infected with the highly pathogenic AIV (HPAIV) H5N1. Through RNA sequencing, we identified novel lncRNAs and analyzed differentially expressed (DE) transcripts at 1 and 3 days post-infection (dpi) in chicken lung tissue. Our results revealed a higher number of DE lncRNAs and mRNAs at 1 dpi and 3 dpi, respectively, compared to control, with resistant chickens exhibiting a notably stronger immune response than susceptible chickens at 3 dpi. Functional analysis implicated these lncRNAs in immune-related pathways crucial for host responses to H5N1 viral infection. Furthermore, we identified lncRNA–mRNA interactions associated with antiviral responses and immune function. Notably, several genes involved in antiviral resistance and immune responses showed higher expression in resistant chickens, confirming their stronger antiviral response. Overall, our study provides insights into the role of lncRNAs in the host's response to HPAIV H5N1 infection in chickens and highlights potential candidates for further investigation into host–pathogen interactions. These findings could drive the development of novel control strategies for AIVs, significantly enhancing poultry health and biosecurity.